Clinicopathologic Features of Gynecologic Malignancies Presenting Clinically as Colonic Malignancies. Issue 1 (24th July 2021) - Fuller, Lanisha D; Dunn, Andrew; Huber, Aaron R; Vyas, Monika; Gonzalez, Raul S
Abstract: Objectives: To systematically evaluate gynecologic malignancies (adnexal or uterine) causing gastrointestinal (GI) signs (eg, mass on colonoscopy) or symptoms (eg, bloody stools) clinically mimicking a GI primary malignancy. Methods: The archives of 2 institutions were retrospectively reviewed for gynecologic malignancies clinically manifesting as colonic lesions. For each case, available radiologic, endoscopic, and histologic findings were recorded. Results: We identified 16 cases: 13 biopsies and 3 resections. The masses were localized in the rectosigmoid (14 cases [88%]), right (1 case [6%]), and transverse (1 case [6%]) colon. Gastrointestinal-type complaints included abdominal pain, weight loss, hematochezia, and obstruction; 1 case was asymptomatic and found during screening colonoscopy. Nine patients (56%) had no known prior gynecologic malignancy, and in only 2 of these patients was there some clinical suspicion of a noncolonic primary malignancy. Most cases (13 [81%]) were serous carcinoma, usually high-grade adnexal or primary peritoneal. Six cases (38%) directly extended into the colon, and 7 (44%) metastasized; route of spread was unclear in the others. Only 1 case (6%) showed mucosal involvement, and none showed desmoplasia or dirty necrosis. Four of the 13 serous carcinomas (31%) showed psammoma bodies. Conclusions: Advanced gynecologic malignancies, most commonly serous carcinoma, can rarely manifest as GI lesions. Clues to noncolonic origin on biopsy include lack of colonic mucosal involvement/dysplasia, desmoplasia, or dirty necrosis.